MAPPING OF CALCIUM AND PHOSPHORUS STATUS OF BUFFALOES IN DIFFERENT CROPPING ZONE OF PUNJAB PROVINCE - M. Z. Khan; T. N. Pasha; U. Farooq; Y. A. Ditta; M. Ilyas; H. Ahmad (Journal of Animal and Plant Sciences, 2012)
The study was conducted to ascertain the calcium and phosphorus imbalances in buffaloes of different cropping zones of Punjab province on the basis of mineral concentrations in blood plasma, feedstuffs, soil and water. Zones selected for studies were central mixed cropping zone (Lahore, Kasur and Okara Districts), Thal irrigated canal zone (Khushab district) and D.G. Khan irrigated zone (Muzaffargarh district). Five sub-locations were selected randomly from each district of the study area. From each sub-location, 10 blood samples were collected each from lactating buffaloes, dry buffaloes and buffalo calves, both in winter and summer season (5 districts x 5 sub-locations x 10 blood samples x 3 physiological stage x 2 seasons = 1500). In addition, a total of 27 feedstuffs (5 districts x 5 sub-locations x 9 feedstuff types x 3 samples for each type x 2 seasons = 1350), 6 soil (5 districts x 5 sub-locations x 6 soil samples x 2 seasons = 300) and 6 water samples (5 districts x 5 sub-locations x 6 water samples x 2 seasons = 300) were collected form each sub-location in both the seasons. Plasma calcium values were found slightly lower in Khushab district, whereas adequate levels were found in Muzaffargarh district. Significant (P>0.05) effects of cropping zones and physiological stages were observed on both calcium and phosphorus concentrations in blood plasma. Whereas, affect of seasons on plasma minerals was found non-significant (P0.05). Feedstuffs of all districts were found variable in calcium and phosphorus content.
Keywords: Calcium; phosphorus; buffaloes; feedstuffs; soil and water